THE IMPORTANCE OF MODERN PEDAGOGICAL TECHNOLOGIES AND THE TEACHINGS OF EASTERN THINKERS IN THE EDUCATION OF PRESCHOOL CHILDREN (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the importance of modern pedagogical technologies and the teachings of Eastern thinkers in the education of preschool children from a scientific and theoretical perspective. At the same time, it is emphasized that combining the spiritual heritage of Eastern thinkers with modern pedagogical technologies is an important factor in the formation of high spiritual and moral qualities in children, and in the upbringing of a well-rounded person who can think independently and creatively.
Keywords: preschool education, modern pedagogical technologies, innovative pedagogical approaches, development of the child's personality, spiritual and moral education, national and universal values, educational process, game technologies, interactive educational methods, the heritage of Eastern thinkers, the teachings of Abu Nasr Al-Farabi, the pedagogical views of Abu Ali ibn Sino, the spiritual heritage of Alisher Navoi.